Did Brand Perceived Quality, Image Product And Place Convenience Influence Customer Loyalty Through Unique Value Proposition? - Bakri; Yulistiana, Ika; Dewi, Roro VemmiKesuma; Nurjaya; Mas'adi, Mahnun; Sunarsi, Denok; Iljasmadi; Erlangga, Heri (The journal of contemporary issues in business and government, 2021)
The purpose of this study was to examine and analyze the effect of brand perceived quality on unique value prepositions, to test and analyze the effect of product brand image on unique value prepositions, to test and analyze the effect of confidence of place on unique value prepositions, to test and analyze the effect of unique value preposition to customer loyalty. This research is a quantitative research with descriptive statistics. The approach used is the survey method. In this study, the respondents were 243 consumers of SMEs products in Tangerang City. Data collection in this study was carried out by means of questionnaires and interviews. Based on the calculation, it can be concluded that brand perceived quality is positive and significant. affect unique value preparation, product brand image positively and significantly affect unique value preparation, confidence of place has a positive and significant effect on unique value preposition, value preposition has a positive and significant effect on customer loyalty.